Keanekaragaman Tumbuhan Berhabitus Pohon di Bantaran Sungai Susup Kabupaten Bengkulu Tengah yang Berpotensi sebagai Mitigasi Bencana - Rizki Yeleni; Bhakti Karyadi; Sutarno Sutarno; Mellyta Uliyandari; Deni Parlindungan; Rendi Zulni Ekaputri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The Susup River is an ecosystem that interacts with living things and their environment. Around the riverbank are various plants, including a tree habitus. Trees around the river have a role in the ecosystem, one of which can prevent flooding. This study aims to identify habitus tree plants that have the potential to be disaster mitigation on the Susup River Bank, Central Bengkulu Regency. The type of research in this study is quantitative descriptive research. Determination of the location of the study using purposive sampling techniques and inventory of tree habitus plants using the square method with the smallest area of 5 m x 5 saplings level, 10 m x 10 m poles level, and 20 m x 20 m trees level. The results of the study found 20 types of tree habitus plants. Of the 20 species of habitus trees found on the banks of the susup river that have the potential for disaster mitigation, there are as many as 15 types. Based on the species diversity index (Shannon-Wiener), the tree level reached 2,730 medium categories, pole levels reached 2,331 medium categories, and sapling levels reached 1,715 medium categories.